Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1080/21645515.2017.1329069
|View full text |Cite
|
Sign up to set email alerts
|

The importance of RSV F protein conformation in VLPs in stimulation of neutralizing antibody titers in mice previously infected with RSV

Abstract: Respiratory syncytial virus (RSV) is a significant respiratory pathogen but no vaccine is available. RSV infections present 2 major, unique problems. First, humans can experience repeated infections caused by the same virus sero-group indicating that protective memory responses to RSV infection are defective. Second, most people have been infected with RSV by age 5. Immune responses to these infections, while poorly protective, could impact the effectiveness of a vaccine. The goal of this study was to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(65 citation statements)
references
References 34 publications
1
64
0
Order By: Relevance
“…It is also possible that RSV G interacts with RSV F on the virus surface, creating a quaternary structure that may limit RSV G to defined structures like those captured by the antibodies discussed in this paper. Interestingly, in an RSV virus-like particle vaccine containing F and G, the conformation of F affected the immunogenicity of G (59). These factors may be important in the design of an RSV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that RSV G interacts with RSV F on the virus surface, creating a quaternary structure that may limit RSV G to defined structures like those captured by the antibodies discussed in this paper. Interestingly, in an RSV virus-like particle vaccine containing F and G, the conformation of F affected the immunogenicity of G (59). These factors may be important in the design of an RSV vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Using prefusion F-and postfusion F-containing VLPs, we assessed the influence of previous RSV infections on neutralizing antibody production in mice. We have reported that, in RSV-experienced mice, a single injection of a prefusion F-containing VLP stimulated high titers of neutralizing antibodies compared to those for postfusion F-containing VLPs or a second RSV infection (26). Here, we further characterized the immune response after VLP immunization of RSV-experienced mice by examining the durability of neutralizing antibody responses as well as levels, avidity, and durability of total anti-F protein IgG antibodies and the numbers of F protein-specific bone marrowassociated long-lived plasma cells and splenic memory B cells.…”
mentioning
confidence: 99%
“…There is some debate over using either pre- or post-fusion F protein conformation. Several recent VLP approaches included the matrix (M) protein from RSV [33], HMPV [34], and NDV [36] and both pre- and post-fusion RSV F protein [33, 34, 36]. In all cases, the VLPs were immunogenic and triggered a desirable Th1 adaptive immune response [33, 34, 36].…”
Section: Virus-like Particles (Vlp)mentioning
confidence: 99%
“…Several recent VLP approaches included the matrix (M) protein from RSV [33], HMPV [34], and NDV [36] and both pre- and post-fusion RSV F protein [33, 34, 36]. In all cases, the VLPs were immunogenic and triggered a desirable Th1 adaptive immune response [33, 34, 36]. Although pre-fusion RSV F protein had a higher neutralizing antibody response than post-fusion RSV F protein, a combination of pre- and post-fusion F proteins produced the strongest Th1 response with the highest proportion of IgG2 antibodies [34].…”
Section: Virus-like Particles (Vlp)mentioning
confidence: 99%